Importance of Hand Eczema in Georgian Population - Matoshvili, Maia; Tophuria, Davit; Kakhniashvili, Inga; Benashvili, Levan; Adamia, Nino (Caucasus Journal of Health Sciences and Public Health, 2016)
Background: Hand eczema, also known as hand dermatitis, is an inflammatory, not contagious skin condition affecting up to 10% of the population. It is characterized by signs of erythema, vesicles, papules, scaling, fissures, hyperkeratosis, and symptoms of itch and pain. It has a major effect on people’s work, social lives and self-esteem. Hand eczema results from a combination of both internal and external factors. It is the most frequent occupational skin disease. The irritant nature of some chemicals means that hand eczema is particularly common in people with jobs involving cleaning, catering, hairdressing, healthcare and mechanical work. The aim of the study was to elucidate the importance of hand eczema in Georgian population. The questionnaire was given to 1500 individuals aged 20-65 years, randomly selected from the population. Individuals considering themselves to have had hand eczema within the previous 12 months were invited to a dermatological examination including patch testing. 721 persons (48%) participated in the study. The 1-year period prevalence of hand eczema was estimated to be about 11% and it was twice common among females than among males. The most common type of hand eczema was irritant contact dermatitis (42%), followed by atopic hand eczema (31%) and allergic contact dermatitis (20%). The most common contact allergies were to nickel, cobalt, fragrance-mix, balsam of Peru and colophony. Comparing these results with a 20-year earlier study on hand eczema, an increased prevalence, especially of atopic hand eczema, was found. The only occupational group that reported a significantly higher period prevalence of hand eczema was service workers. Of all occupations, cleaners had the highest period prevalence 35%. Hand eczema was more common among people reporting some kind of occupational exposure. The most harmful exposure turned out to be to unspecified chemicals, water and detergents and dust and dry dirt. Hand eczema was shown to be a long-lasting disease with a relapsing course. 67% of the patients had consulted a doctor and 32% had been on sick-leave at least once because of their hand eczema. Results: Treatment with topical steroids was reported by 57%, emollients by 90%. Frequent itching was reported by 60% of the patients. 81% experienced some kind of disturbance of their daily life considered to be caused by the hand eczema. A multiple logistic regression analysis revealed that the most important predictive factor for hand eczema was a history of childhood eczema. Number two was female sex, followed by occupational exposure, a history of atopic dermatitis and/or asthma and a service occupation.